No girls allowed - "Pascal, Francine" (Bantam Books: New York, 1995)
Elizabeth Wakefield is the star of the Sweet Valley Soccer League. Her good friend Todd Wilkins plays on the team, too. But suddenly the other boys are teasing Todd, saying that Elizabeth is his "girlfriend." Now Todd is being mean to Elizabeth. He says she's not good at sports just because she's a girl! Playing soccer isn't fun anymore, so Elizabeth quits. But without their best player, the soccer team can't win! Can the team get Elizabeth back?
Keywords: Soccer Fiction